Optimasi Validitas Dan Reliabilitas Tes Pilihan Ganda Buatan Guru Mata Pelajaran Matematika Kelas Iv Sekolah Dasar - Novi Dwantari; Ahmad Rustam; Ashari Usman (Prodi PGSD Unsultra, 2021)
This study aims to examine the validity and reliability of test items using the Rasch model on teacher-made test questions in elementary schools. The use of the Rasch model for validity and reliability testing helps teachers to evaluate and improve the quality of their tests so that they can more accurately measure students’ abilities and better understand their learning progress. This research combines quantitative and development approaches, focusing on analyzing a teacher-developed multiple-choice test in the subject of mathematics. The test subjects in this study were the teacher-made test items and students from grades IV, V, and VI at SD Negeri 5 Wiwirano and SD Negeri 6 Wiwirano, with a total of 100 students (50 students from each school). Data collection was conducted through a test trial, which provided scores used to determine the quality of the test items. The data were analyzed through assumption testing, item analysis, reliability analysis, and bias detection using the Rasch model. The results of the study showed that all 20 test items were categorized as valid, and there were no biased items detected. This indicates that the Rasch model is effective for assessing the quality of test items. Therefore, validity and reliability testing are essential components of the evaluation process, and the Rasch model with the Winstep application can serve as a reliable tool for item analysis and improving test quality.